Transforming Logistics Education in Higher Institutions: The Role of Digital Technologies in Global Training Contexts - Abdillah, Muhammad Rifqy Naufal; Wahyuilahi, Muhammad (Sinergi International Journal of Logistics, 2025)
This paper explores the current state of digital logistics education and training, emphasizing the integration of advanced technologies such as virtual reality, digital twins, and artificial intelligence. The purpose of the study is to examine the impact of these technologies on learning outcomes and to identify the barriers that limit their effectiveness. A comprehensive literature review was conducted using databases such as Scopus and Google Scholar, with a focus on studies related to digital education, logistics, and technological adoption. The findings reveal that technologies such as virtual reality (VR) significantly improve engagement and concept mastery in logistics simulations, while artificial intelligence (AI) enhances personalized learning pathways. However, challenges such as insufficient infrastructure. The review highlights the importance of aligning curricula with industry needs and fostering greater collaboration between academia and industry. Policy recommendations include investing in digital infrastructure, enhancing educator training, and designing inclusive curricula that can accommodate diverse student populations. The study concludes with recommendations for future research to explore the long-term effects of digital training and the development of standardized evaluation methods for emerging educational technologies in logistics.